The Lack of Preventive Protection and Judicial Inactivity in the Enforcement of Security Interests: A Perspective on Dignified Justice - Firman Hasurungan Simanjuntak; Diana R. W. Napitupulu; Andrew Betlehn (Eduvest - Journal of Universal Studies, 2026)
The execution of Mortgage Rights (Hak Tanggungan) often places Third-Party Guarantors in a vulnerable position due to the lack of adequate legal protection instruments. This study aims to analyze the void of preventive protection norms in Indonesia's auction regulations and critique the judges' considerations in the South Jakarta District Court Decision Number 1059/Pdt.G/2022/PN JKT. SEL through the analytical lens of the Dignified Justice Theory. This research is normative legal research using statutory, conceptual, and case approaches. The results reveal two main conclusions. First, there is a legal vacuum in the Mortgage Rights Law and Minister of Finance Regulation No. 213/PMK.06/2020, which do not accommodate the right to rebut against the determination of the Limit Value, thereby legitimizing unilateral predatory pricing practices by the holder of executorial rights. Second, the Panel of Judges was proven to be trapped in a rigid positivism paradigm (la bouche de la loi) and failed to conduct legal discovery (rechtsvinding) to uncover the anomaly of auction prices that fell below the liquidation value. The decision failed to humanize humans (nguwongke uwong) and violated substantive justice. This study recommends regulatory reconstruction through the institutionalization of a "Rebuttal Period" in the pre-auction phase and the urgency of issuing a Supreme Court Circular Letter (SEMA) to encourage judicial activism in canceling exploitative auctions.